Introducing Cooperative Learning for ELT in Chile: Two Teachers’ Perceptions and Use - Soffía; de la Barra-Van Treek, Erika (Revista de Estudios y Experiencias en Educación, 2024)
This paper reports on a qualitative study of the perceptions of two English teachers about their adoption of cooperative learning in two vulnerable schools in Santiago. The study aimed to examine the preconceptions, expectations and apprehensions that prevent teachers from incorporating more interactive methodologies, such as cooperative learning and content-based approaches, when teaching English as a foreign language, such as cooperative learning and content-based approach thus perpetuating the use of more traditional approaches like the grammar translation method. Data were collected through rubrics from classroom observations, teachers' reflective journals, and teachers’ semi-structured interviews. Data were coded according to the model provided by Creswell (2013), which allowed us to categorize themes that later were interpreted in the context of the study. The results showed that both teachers found the experience useful and helped them realize how important their role as agents of change is. Nonetheless, the results also suggest that teachers face important challenges when introducing cooperative learning at schools, which are related to the school communities' culture and what is expected from teachers. An implication of the findings was that when teachers introduce cooperative learning, they should incorporate a formative phase to help students understand the dynamics of this approach.